Social support and caregiver burden: an integrative review - Rodríguez-Lombana, Lorena; Chaparro-Díaz, Lorena (Revista Cuidarte, 2020)
Introduction: Through an integrative review, this study aims to describe the social support interventions on family caregivers of patients with Chronic Non-Communicable Diseases that modify the perception of caregiver burden. Materials and Methods: An integrative descriptive review of the literature was conducted for the search of articles correlated to the phenomenon over the last 10 years, which were potentially relevant to identify, evaluate and integrate the conclusions on social support interventions that modify caregiver burden. Methodological rigor was ensured following the parameters established by Whittemore and Knafl for data submission under the PRISMA Statement. Results: The prism of social support is observed in family caregivers of patients with Chronic Non-Transmissible Diseases with a sample of 19 pieces of research analyzed (9 quantitative articles, 7 qualitative articles, and 3 mixed articles), following a 100% nursing approach. An analysis was made based on the categories of caregivers’ profile, burden (physical and emotional), nursing care (through social support: informational, emotional and continuous care) and social support interventions ranging from educational to emotional aspects. A gap in instrumental support was found as we did not find any outcomes associated with this component in nursing interventions. Discussion: Most studies identified that most interventions were individual, group/family or the combination of family group and individual. Conclusions: Social support interventions on family caregivers have a positive influence on reducing caregiver burden. Interventions at the rural level are also required to address instrumental support. Como citar este artículo: Rodríguez-Lombana L, Chaparro-Diaz L. Soporte social y sobrecarga en cuidadores: Revisión integrativa. Rev Cuid. 2020; 11(1): e885. http://dx.doi.org/10.15649/cuidarte.885